ICT-FLAG: a web-based e-assessment platform featuring learning analytics and gamification. Issue 1 (18th April 2017) - Gañán, David; Caballé, Santi; Clarisó, Robert; Conesa, Jordi; Bañeres, David
Abstract : Purpose: The purpose of this paper is to present an innovative web-based eLearning platform called ICT-FLAG that provides e-assessment tools with general-purpose formative assessment services featuring learning analytics and gamification. Design/methodology/approach: The paper reports on the technical development of the platform driven by the Reference Model for Open Distributed Processing software methodology, which guides the platform construction, including the analysis and design steps. Findings: The ICT-FLAG platform is technically tested by integrating it into a real e-assessment tool. Results are positive in terms of functional and non-functional aspects as well as user's satisfaction on usability, emotional state, thus validating the platform as a valuable educational tool. Research limitations/implications: Because of the chosen technical paper as article type, validation of the impact of the ICT-FLAG platform in the learning process is not provided. Ongoing research with this platform is to measure the learning outcomes of its use in a real context of eLearning. Practical implications: The paper shows implications of the main technical issues and challenges encountered during the integration of the ICT-FLAG platform with external eLearning tools, involving relevant aspects of interoperability, security, modularity, scalability, portability and so on. Originality/value: This platform can fill the gap of many e-assessment systems, which currently do not have built-in analytical and gamification tools for learning, thus providing them with the experience to improve the quality of education and learning.